Genetische Diagnostik bei psychischen Erkrankungen im Erwachsenenalter: Übersichten - Kilarski, Laura L.; Claus, Isabelle; Binder, Elisabeth B.; Degenhardt, Franziska; Domschke, Katharina; Forstner, Andreas Josef; Grabe, Hans Jörgen; Heilbronner, Urs; Müller, Daniel; Nöthen, Markus Maria; Radtke, Franziska; Rietschel, Marcella; et al. (Der Nervenarzt, 2024)
This review article provides insights into the role of genetic diagnostics in adult mental health disorders. The importance of genetic factors in the development of mental illnesses, from rare genetic syndromes to common complex genetic disorders, is described. Current clinical characteristics that may warrant a genetic diagnostic work-up are highlighted, including intellectual disability, autism spectrum disorders and severe psychiatric conditions with specific comorbidities, such as organ malformations or epilepsy. The review discusses when genetic diagnostics are recommended according to current guidelines as well as situations where they might be considered even in the absence of explicit guideline recommendations. This is followed by an overview of the procedures and the currently used diagnostic methods. Current limitations and possible developments in the field of genetic diagnostics in psychiatry are discussed, including the fact that, for many mental health conditions, genetic testing is not yet part of standard clinical practice; however, in summary genetic causes should be considered more frequently in certain clinical constellations, and genetic diagnostics and counselling should be offered where appropriate.